'Tough and tender'? Agricultural masculinities and fathering activities. Issue 4 (2nd October 2019) - Brandth, Berit
ABSTRACT: The article is concerned with how hegemonic masculine activities comply with farming fathers' caregiving to possibly change masculinity and produce gender equality. Based on interviews with farming fathers, several activities with children are narrated as part of their fathering practices, such as hunting, outdoor leisure activities. Being firmly within traditional male areas they serve to uphold hegemonic masculinity. This notwithstanding, combined with caregiving, they show a fluidity and hybridization of masculinity in which the 'tough' is combined with the 'tender.' The fathers also report avoiding prioritizing work at the expense of their children and that they do more caregiving in the home than previous generations, although mothers are still in charge. This implies blurring, but nevertheless conservation, of gender boundaries. A dismantling of rural hegemonic masculinity still seems to be a distance away.